ANALISIS BIBLIOMETRIK : PENERAPAN PEMBELAJARAN MENDALAM DAN PENGARUHNYA TERHADAP BERPIKIR KRITIS SISWA - Windu Kusmawati; Zaenal Abidin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
21st-century education demands a paradigm shift toward developing higher-order cognitive skills, with critical thinking skills being one of the most crucial competencies. To stimulate this ability, current literature highly emphasizes the importance of a deep learning approach. This study aims to map the scientific publication trends regarding the implementation of deep learning and its relationship with students' critical thinking skills using bibliometric analysis. Data were retrieved from the Google Scholar database using Harzing’s Publish or Perish (PoP) application within the 2024–2026 period, yielding a sample of 15 academic documents. The dataset was then analyzed and visualized using VOSviewer software to map the co-authorship networks and keyword co-occurrences. The quantitative analysis results show dynamic growth in literature, with a significant spike in publications occurring in 2025, reaching 73.33% of the total documents. This surge was a direct impact of national curriculum policy interventions in Indonesia regarding the planned implementation of this approach. The co-authorship network analysis reveals a balanced collaboration with a relatively uniform intensity of contribution among four main authors. Meanwhile, the density-based keyword co-occurrence analysis highlights that the terms